Striational Muscle Antibody Positivity Heralding a Diagnosis of Autoimmune Encephalitis associated with Epiglottic Squamous Cell Carcinoma: A Case Report (Global Journal of Medical Research, 2020)
A 59 yo woman presented to our emergency room with confusion, spells of loss of awareness over four weekswith malaise, weakness, gait difficulties, and 30 lb weight loss over one year. Brain imaging was unremarkable. EEGs revealed diffuse slowing, triphasic GPDs, and left temporal epileptiform discharges. Spinal fluid showed an elevated protein count. She received a working diagnosis of autoimmune encephalitis and received steroids and antiepileptic medications. She experienced an improvement in symptoms and went home. Follow up revealed elevated striational muscle antibodies and enhancement of spinal nerve roots suggesting an autoimmune neurological syndrome. She received intravenous immune globulin (IVIg) therapy and had periods of improvement followed by worsening a few months later with each dose of IVIg. She presented to the hospital a year with worsening dysphagia and an endoscopy showing an epiglottic mass. Pathology confirmed squamous cell carcinoma, and she received chemotherapy and radiation. We wish to share this rare case of autoimmune encephalitis presenting with only striational antibodies as a heralding sign of a tumor. We postulate that, in the correct context, the presence of striational antibodies alone, despite low titers, may support a diagnosis of autoimmune encephalitis from underlying malignancy.
Keywords: epilepsy; autoimmune encephalitis; striational antibodies